Recognized characteristics of exemplary teachers in university settings from the perspective of educational college students - Nidham Abdul Jabbar Hussein; Rizgar Hamalaw Khalid (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
Education and the types of education enable the university to achieve the goals and objectives of the members, the staff of lecturers of the university education from the point of view of various students, the role of university lecturers in the modern education system as the Instructor has a key role in the process of education. The area of research is limited at Sulaimaniah University including College of Basic Education and College of Education for human Sciences- Said sadq in (2017-2018). The method of research is descriptive , the total number is (1302), the sample included (135) students of both genders randomly from the departments of the College of Basic Education and the College of Education for human Sciences Sidesadeq / University of Sulaymaniyah both researchers used the questionnaire as a tool to collect data with the total dependence on the extraction (static average) ; synchronized with this made some recommendations (including the attention to all aspects of personality and psychological, social, experience ,scientific and educational) in the classes. Some suggestions have been accomplished.